Debates about Educational Issues: A Pedagogical Strategy to Explore Argumentative Skills in the EFL Classroom - Ángela Vanesa Duarte Infante; Sandra Milena Fonseca Velandia; Bertha Ramos Holguín (Asociación Colombiana de Profesores de Ingles, 2020)
This article describes a pedagogical proposal, based on debates, to determine the type of arguments that pre-service English language teachers constructed at a public university in Tunja, Colombia. We implemented a series of debate workshops about educational issues. Thirteen modern languages pre-service teachers in their sixth semester participated in the debates. In each debate, we collected data through recordings, focus groups, and field notes to understand the impact of the pedagogical intervention. Findings suggest that the arguments pre-service teachers built were based on examples. In this sense, the arguments built were based on their personal experiences and their partners' opinions. We argue for the need to implement more research proposals that will contribute to the understanding and awareness of what argumentation implies.